DATA PROCESSING SYSTEM DESIGN INFORMATION STUDENTS SCHOOL COST AND DATA ON AL-HUSNA KINDERGATEN USING MICROSOFT VISUAL BASIC 6.0 - Finna Rachmania; Yudi Irawan Chandra, Skom, MMSI (Jurnal Sistem Informasi, 2005)
This writing explains the data processing system of student tuition and data on Al -Husna Kindergaten that during this process is still done manually, so much thepossibility of error. Therefore, the authors provide a better alternative to create a dataprocessing system of student tuition and a computerized data by using Visual Basic6.0 programming language, the authors propose to help students process dataprocessing, data school cost.